Adaptable Blockchain-Based Systems: A Case Study for Product Traceability - Lu, Qinghua; Xu, Xiwei (IEEE software, 2017)
Tracing the origin of products across complex supply chains requires a transparent, tamper-proof metadata infrastructure that's not only trusted by all the involved parties but also adaptable to changing environments and regulations. Can such advanced infrastructure be implemented in a decentralized way? Qinghua Lu and Xiwei Xu share their story of developing the originChain system, which leverages emerging blockchain technology to do so.